AI-Powered Financial Reporting Chatbots: Transforming Insurance Industry Operations - Chetan Prakash Ratnawat, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the transformative impact of AI-powered financial chatbots in the insurance industry, focusing on the evolution from traditional manual processes to automated solutions. The article investigates technical architecture, role-specific functionality, security frameworks, and performance analytics across major insurance organizations worldwide. Through extensive research and analysis, this article demonstrates how intelligent automation addresses traditional inefficiencies in insurance operations while enhancing data accuracy, improving security protocols, and delivering substantial operational benefits. The findings reveal that insurance companies implementing these advanced systems experience significant improvements in underwriting efficiency, agent productivity, security compliance, and overall operational effectiveness while maintaining robust data protection standards and regulatory compliance.
Keywords: Insurance Technology Integration; AI-Driven Financial Reporting; Insurance Process Automation; Cybersecurity in Insurance; Predictive Analytics for Insurance